Characterization of the biocontrol activity of three bacterial isolates against the phytopathogen Erwinia amylovora. Issue 3 (7th June 2021) - Dagher, Fadi; Nickzad, Arvin; Zheng, Jie; Hoffmann, Maria; Déziel, Eric
Abstract: Antibiotics are sprayed on apple and pear orchards to control, among other pathogens, the bacterium Erwinia amylovora, the causative agent of fire blight. As with many other pathogens, we observe the emergence of antibiotic‐resistant strains of E . amylovora . Consequently, growers are looking for alternative solutions to combat fire blight. To find alternatives to antibiotics against this pathogen, we have previously isolated three bacterial strains with antagonistic and extracellular activity against E . amylovora, both in vitro and in planta, corresponding to three different bacterial genera: Here, we identified the inhibitory mode of action of each of the three isolates against E . amylovora . Isolate Bacillus amyloliquefaciens subsp. plantarum (now B . velezensis ) FL50S produces several secondary metabolites including surfactins, iturins, and fengycins. Specifically, we identified oxydifficidin as the most active against E . amylovora S435. Pseudomonas poae FL10F produces an active extracellular compound against E . amylovora S435 that can be attributed to white‐line‐inducing principle (WLIP), a cyclic lipopeptide belonging to the viscosin subfamily (massetolide E, F, L, or viscosin). Pantoea agglomerans NY60 has a direct cell‐to‐cell antagonistic effect against E . amylovora S435. By screening mutants of this strain generated by random transposon insertion with decreased antagonist activity against strain S435, we identified several defective transposants. Of particular interest was a mutant in a gene coding for a Major Facilitator Superfamily (MFS) transporter corresponding to a transmembrane protein predicted to be involved in the extracytoplasmic localization of griseoluteic acid, an intermediate in the biosynthesis of the broad‐spectrum phenazine antibiotic D ‐alanylgriseoluteic acid. Abstract : Antibiotics are sprayed on apple and pear orchards to control the bacterium Erwinia amylovora, the causative agent of fire blight. Growers are looking for solutions to combat this disease. We have previously isolated three bacterial strains with antagonistic activity against E. amylovora . Here, we identified their inhibitory mode of action. Isolate B acillus velezensis FL50S produces several secondary metabolites including oxydifficidin as the most active against E. amylovora S435. Pseudomonas poae FL10F produces a cyclic lipopeptide belonging to the viscosin subfamily. Pantoea agglomerans NY60 has a direct cell‐to‐cell antagonistic effect against E. amylovora S435. By screening mutants with decreased antagonist activity against strain S435, we identified a gene predicted to be involved in the biosynthesis of the broad‐spectrum phenazine antibiotic D‐alanylgriseoluteic acid.